Kesalahan-kesalahan penerapan bahasa Indonesia dalam berkomunikasi pada masyarakat bolaang Mongondow, Sulawesi Utara - Amboy, Abdul Givari Ratama (Maliki Interdisciplinary Journal, 2024)
A B S T R A C T Mongondow language is one of the regional languages in Indonesia, which must be preserved by being used frequently in everyday life. However, we must not forget to familiarize the Indonesian language in everyday life as a form of love for the nation. This research aims so that we can find out what are the mistakes of the Bolaang Mongondow in applying the national language in everyday life. Apart from that, it is also so that we know what are the factors and causes of the difficulty for the Bolaang Mongondow community to apply the national language in everyday life. In addition, so that we know what are the factors and causes of Bolaang Mongondow people find it difficult to apply the national language in everyday life. In addition, so that we know what are the factors and causes of Bolaang Mongondow people find it difficult to apply the national language in everyday life. The method in this study is a qualitative descriptive method based on interviews, observations, and FGDs. Then it is synchronized with the data that The authors get the findings in this study is that people lack the application of the national language in everyday life.